2019
DOI: 10.1002/chem.201904675
|View full text |Cite
|
Sign up to set email alerts
|

An Unsymmetrical Squaraine‐Based Activatable Probe for Imaging Lymphatic Metastasis by Responding to Tumor Hypoxia with MSOT and Aggregation‐Enhanced Fluorescent Imaging

Abstract: Optoacoustic imaging has great potential for preclinicalr esearch andc linical practice, and designing robust activatable optoacoustic probes for specific diseases is beneficial for its further development. Herein, an activatable probe has been developed for tumor hypoxia imaging. For this probe,i ndole and quinoline were linked on each side of an oxocyclobutenolate core to form an unsymmetrical squaraine. At riarylamine group was incorporated to endow the molecule with the aggregation enhanced emission (AEE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 111 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…Reproduced with permission: Copyright 2019, Wiley-VCH GmbH. [233] (F) Schematic illustration of the reaction of nanoprobe 99a with NTR in a tumor (top) and two image scenarios of breast tumor metastasis (bottom). Reproduced with permission: Copyright 2019, Wiley-VCH GmbH.…”
Section: Aiegens For Cathepsin Bmentioning
confidence: 99%
“…Reproduced with permission: Copyright 2019, Wiley-VCH GmbH. [233] (F) Schematic illustration of the reaction of nanoprobe 99a with NTR in a tumor (top) and two image scenarios of breast tumor metastasis (bottom). Reproduced with permission: Copyright 2019, Wiley-VCH GmbH.…”
Section: Aiegens For Cathepsin Bmentioning
confidence: 99%
“…Recently, quite a few NTR-activatable optical probes or theranostic systems have been reported. [38][39][40][41][42][43][44][45][46][47][48][49] The general working mechanisms are summarized in Figure 4.…”
Section: Reductasementioning
confidence: 99%
“…A number of activatable NIR FL probes (e.g., 7-9) have been successfully obtained by means of the nitro-to-amino transformation strategy, demonstrating the feasibility of this means. [44][45][46][47][48][49] The work shown in Figure 5 is a good example to the strategy I. The nanoprobe developed by Zeng and Wu et al through the self-assembly of Q-NO 2 (i.e., compound 10) is NTR-activatable for the imaging of breast cancer metastases via NIR-I/NIR-II FL imaging and MSOT imaging.…”
Section: Reductasementioning
confidence: 99%
“…injection of the nanoprobe, PA imaging of a 4T1 subcutaneous tumor bearing mice displayed contrast at the tumor and indicated the hypoxic regions as a reflection of tumor heterogeneity. [211] A similar nanoparticle-based approach utilized bioreductive properties with azoreductase-responsive PA probes. Huang et al reported a xanthene dye conjugated to N-phenyldiethanolamine via an azo linker (NR-azo).…”
Section: Multispectral Photoacoustic Tomographymentioning
confidence: 99%